Learning Impromptu Speech through Peer Activity to Enhance Students' Speaking Competence - Herawati, Reni (Caraka Olah Pikir Edukatif, 2010)
This research aiming at describing: the effectiveness of the technique of Learning Impromptu Speech through Peer Activity at SMA 5 Yogyakarta; how the technique could enhance speaking capability among students of SMA N 5 Yogyakarta. This research is action research. The findings have shown that there was a significant improvement in their speaking capabilitie. They were getting better gradually in developing and organizing idea. This learning technique could guide students to become better, autonomous, and confident learners. The students were encouraged to depend more on themselves instead of the teacher.